CCNA Cyber Ops SECFND 210-250 official cert guide - Santos, Omar; Muniz, Joseph; De Crescenzo, Stefano (Cisco Press, 2017)
CCNA Cyber Ops SECFND 210-250 Official Cert Guide from Cisco Press allows you to succeed on the exam the first time and is the only self-study resource approved by Cisco. Cisco enterprise security experts Omar Santos, Joseph Muniz, and Stefano De Crescenzo share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. This complete study package includes A test-preparation routine proven to help you pass the exam Do I Know This Already? quizzes, which allow you to decide how much time you need to spend on each section Chapter-ending exercises, which help you drill on key concepts you must know thoroughly The powerful Pearson Test Prep practice test software, with two full sample exams containing 120 well-reviewed, exam-realistic questions, customization options, and detailed performance reports A final preparation chapter, which guides you through tools and resources to help you craft your review and test-taking strategies Study plan suggestions and templates to help you organize and optimize your study time Well regarded for its level of detail, study plans, assessment features, challenging review questions and exercises, this official study guide helps you master the concepts and techniques that ensure your exam success. The official study guide helps you master topics on the CCNA Cyber Ops SECFND 210-250 exam, including: Network concepts Security concepts Cryptography Host-based analysis Security monitoring Attack methods.